An intermittent schedule is better than continuous regimen of antimonial therapy for cutaneous leishmaniasis in the municipality of Rio de Janeiro, Brazil - Azeredo-Coutinho,Rilza Beatriz G. de (2002)
This study reviews a series of cutaneous leishmaniasis cases diagnosed and treated in outpatient units in the municipality of Rio de Janeiro, where the intermittent schedule of antimonial therapy was replaced by the continuous regimen. Both schedules were based on daily intramuscular injections of pentavalent antimonial. Forty-nine subjects received the intermittent regimen, consisting of three ten-day series alternated with ten-day rest intervals whereas seventy-one patients received the continuous regimen during 20 consecutive days. The study groups had similar composition regarding age, sex and clinical condition. The cure rate was significantly higher in the group receiving the intermittent schedule than in the group receiving continuous therapy (89.8% vs 63.3%). Moreover, loss to follow-up was significantly more frequent in the group receiving continuous therapy (19.7% vs 4.1% in the intermittent therapy). Under field conditions, the intermittent regimen provided higher effectiveness and adherence than the continuous schedule.